SH2 Domain-Mediated Interaction of Inhibitory Protein Tyrosine Kinase Csk with Protein Tyrosine Phosphatase-HSCF - Wang, Bing (American Society for Microbiology, 2001)
The protein tyrosine kinase (PTK) Csk is a potent negative regulator of several signal transduction processes, as a consequence of its exquisite ability to inactivate Src-related PTKs. This function requires not only the kinase domain of Csk, but also its Src homology 3 (SH3) and SH2 regions. We showed previously that the Csk SH3 domain mediates highly specific associations with two members of the PEP family of nonreceptor protein tyrosine phosphatases (PTPs), PEP and PTP-PEST. In comparison, the Csk SH2 domain interacts with several tyrosine phosphorylated molecules, presumed to allow targetting of Csk to sites of Src family kinase activation. Herein, we attempted to understand better the regulation of Csk by identifying ligands for its SH2 domain. Using a modified yeast two-hybrid screen, we uncovered the fact that Csk associates with PTP-HSCF, the third member of the PEP family of PTPs. This association was documented not only in yeast cells but also in a heterologous mammalian cell system and in cytokine-dependent hemopoietic cells. Surprisingly, the Csk–PTP-HSCF interaction was found to be mediated by the Csk SH2 domain and two putative sites of tyrosine phosphorylation in the noncatalytic portion of PTP-HSCF. Transfection experiments indicated that Csk and PTP-HSCF synergized to inhibit signal transduction by Src family kinases and that this cooperativity was dependent on the domains mediating their association. Finally, we obtained evidence that PTP-HSCF inactivated Src-related PTKs by selectively dephosphorylating the positive regulatory tyrosine in their kinase domain. Taken together, these results demonstrate that part of the function of the Csk SH2 domain is to mediate an inducible association with a PTP, thereby engineering a more efficient inhibitory mechanism for Src-related PTKs. Coupled with previously published observations, these data also establish that Csk forms complexes with all three known members of the PEP family.